Rational Design of a New Class of Toll-Like Receptor 4 (TLR4) Tryptamine Related Agonists by Means of the Structure- and Ligand-Based Virtual Screening for Vaccine Adjuvant Discovery - Honegr, Jan; Dolezal, Rafael; Malinak, David; Benkova, Marketa; Soukup, Ondrej; Almeida, Joyce S F D de; Franca, Tanos C C; Kuca, Kamil; Prymula, Roman (Molecules, 2018)
In order to identify novel lead structures for human toll-like receptor 4 (hTLR4) modulation virtual high throughput screening by a peta-flops-scale supercomputer has been performed. Based on the in silico studies, a series of 12 compounds related to tryptamine was rationally designed to retain suitable molecular geometry for interaction with the hTLR4 binding site as well as to satisfy general principles of drug-likeness. The proposed compounds were synthesized, and tested by in vitro and ex vivo experiments, which revealed that several of them are capable to stimulate hTLR4 in vitro up to 25% activity of Monophosphoryl lipid A. The specific affinity of the in vitro most potent substance was confirmed by surface plasmon resonance direct-binding experiments. Moreover, two compounds from the series show also significant ability to elicit production of interleukin 6.
Keywords: Animals; Molecular Dynamics Simulation; Surface Plasmon Resonance; povrchová plasmonová rezonance; vakcíny; CHO buňky; Inhibitory Concentration 50; vazebná místa; počítačová simulace; rychlé screeningové testy; simulace molekulového dockingu; toll-like receptor 4; Adjuvants, Immunologic; tryptaminy; Structure-Activity Relationship; lidé; simulace molekulární dynamiky; High-Throughput Screening Assays; inhibiční koncentrace 50; Interleukin-6; Vaccines; Tryptamines; Cricetulus; Computer Simulation; Ligands; Toll-Like Receptor 4; interleukin-6; vztahy mezi strukturou a aktivitou; CHO Cells; zvířata; adjuvancia imunologická; Molecular Docking Simulation; ligandy; Binding Sites; Humans